# How do you solve #(x - 2)/ 3 = 1/ x#?

Multiply Crosswise:

This leaves us with a quadratic equation, which we can further factor:

Using the null factor law, we can now solve the following by figuring out the numbers that cause each bracket to equal zero:

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (x - 2)/3 = 1/x, we can start by cross-multiplying to eliminate the fractions. This gives us (x - 2) * x = 3 * 1. Expanding the left side of the equation, we have x^2 - 2x = 3. Rearranging the equation, we get x^2 - 2x - 3 = 0. This is a quadratic equation, which can be factored as (x - 3)(x + 1) = 0. Setting each factor equal to zero, we find x = 3 or x = -1. Therefore, the solutions to the equation are x = 3 and x = -1.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- If Y varies directly as x and inversely as the square of z. y=20 when x=50 and z =5. How do you find y when x=3 and z=6?
- How do you evaluate #(5a - 5) ( 9a ^ { 2} - 9a - 2)#?
- How do you solve #6 / (x-4) + 9/x = -36/(x^2 - 4x)#?
- How do you multiply and simplify #\frac { y ^ { 2} - 9} { 6y - 18} \cdot \frac { y + 5} { y + 3}#?
- How do you simplify #(5x^2+10x)/(x^2-x-6)div(15x^3+45x^2)/(x^2-9)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7